2000
DOI: 10.1093/oxfordjournals.molbev.a026298
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Occurrence of Spliceosomal Introns in the rDNA Genes of Ascomycetes

Abstract: Spliceosomal (pre-mRNA) introns have previously been found in eukaryotic protein-coding genes, in the small nuclear RNAs of some fungi, and in the small- and large-subunit ribosomal DNA genes of a limited number of ascomycetes. How the majority of these introns originate remains an open question because few proven cases of recent and pervasive intron origin have been documented. We report here the widespread occurrence of spliceosomal introns (69 introns at 27 different sites) in the small- and large-subunit n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 66 publications
2
78
0
Order By: Relevance
“…These results indicate that the ribosomal RNA genes have higher rates of heterogeneity among lineages than protein coding genes. This may not be unexpected as these genes include more insertions (DNA regions highly affected by mutations) compared with other genes, in fungi (Bhattacharya et al, 2000; DePriest, 2004;Simon et al, 2005;Hofstetter et al, 2007), and some of such insertions may have remained in our final dataset.…”
Section: Difference In Sequence Evolution Ratementioning
confidence: 90%
See 1 more Smart Citation
“…These results indicate that the ribosomal RNA genes have higher rates of heterogeneity among lineages than protein coding genes. This may not be unexpected as these genes include more insertions (DNA regions highly affected by mutations) compared with other genes, in fungi (Bhattacharya et al, 2000; DePriest, 2004;Simon et al, 2005;Hofstetter et al, 2007), and some of such insertions may have remained in our final dataset.…”
Section: Difference In Sequence Evolution Ratementioning
confidence: 90%
“…These results indicate that the ribosomal RNA genes have higher rates of heterogeneity among lineages than protein coding genes. This may not be unexpected as these genes include more insertions (DNA regions highly affected by mutations) compared with other genes, in fungi (Bhattacharya et al, 2000; DePriest, 2004;Simon et al, 2005;Hofstetter et al, 2007), and some of such insertions may have remained in our final dataset.Heterogeneity in substitution rates among lineages is a common observation in molecular phylogenetic studies (Lutzoni and Pagel, 1997;Allen et al, 2006;Lumbsch et al, 2008;Smith and Donoghue, 2008). In the present study, we found significant rate heterogeneity between the wet-tropical/moist-temperate clade ABC and the rest of the lineages (Table 4), which together with the comparatively longer branches in clade ABC, suggests that this clade evolves faster than the other lineages.…”
mentioning
confidence: 90%
“…Convergent intron insertion has been invoked to account for some patchy intron phylogenetic distributions (33)(34)(35)(36). Perhaps the strongest case is that reported in several species of Chironomus by Hankeln …”
Section: Discussionmentioning
confidence: 99%
“…The first available molecular data, provided by Bhattacharya et al (2000), suggested that Porina formed part of Lecanoromycetes, specifically being sister to Stereocaulon in the Lecanorales; this, however, stemmed from the sequences of the species used (P. guentheri) apparently being incorrectly labelled or from contaminants (the nuSSU appears to be part of Dothideomycetes, whereas the nuLSU is suggested to belong to Parmeliaceae and includes a rare intron). Nevertheless, the placement of Porinaceae in Lecanoromycetes was subsequently shown by Grube et al (2004), who demonstrated that it belonged in Ostropomycetidae, not Lecanoromycetidae, close to taxa in Ostropales.…”
Section: Introductionmentioning
confidence: 99%